Evaluasi Mine Dewatering Terhadap SUMP4 Mengunakan Pompa MF420 EXHV & MF210 MV PT. Indomining Sangasanga Kabupaten Kutai Kartanegara Provinsi Kalimantan Timur - William William; Shalaho Dina Devy; Sakdillah Sakdillah; Agus Winarno; Albertus Juvensius Pontus (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2024)
The combination of a fully dedicated and comprehensive infrastructure, close proximity to ports, an integrated supply chain and strategic synergies with other subsidiaries within the Group, has driven rapid and cost-effective growth.